Studi Aplikasi Metode Potensiometri Pada Penentuan Kandungan Karbon Organik Total Tanah - Abdul Haris Watoni; Buchari Buchari (Institut Teknologi Bandung, 2000)
STUDI APLIKASI METODE POTENSIOMETRI PADA PENENTUAN KANDUNGAN KARBON ORGANIK TOTAL TANAH In recent years, ion selective electrodes have become more useful for the determination of certain ion in solutions rather than in soil system. The applications of potentiometric for the determination of the total soil organic carbon has been investigated with CO2 selective electrode as indicator electrode. The principle of the determination is base on the conversion of total soil organic carbon in the sample to CO2 and than the CO2 produced was measured potentiometrically by CO2 selective electrode. The concentration of CO2 was proportional with the total soil organic carbon in the samples. Before application for the measurement, the CO2 selective electrode must be characterized. The investigation showed that the respon time of the electrode was 2,5 minutes and it was stable for 40 seconds because the lost of CO2 to the air. The range of concentration for the measurement was between 9.09 x 10-4 M to 3.83 x 10 -1M of CO2 with the Nernst factor was 53 mV per decade and the limit of detection was 4.5 x 10-4 M of CO2 and the optimum pH of the solution was 4.8. The present of CH3COO- and H2PO4- over 10-2 M in concentrations interfered the measurement of CO2 with their potentiometric coefficient of selectivity was 0.36 and 0.133 respectively. The validity of potentiometric method for the determination of the total soil organic carbon was compared with the titrimetric method for the same samples. This investigation showed that the potentiometric method was applicable to the determination of the total soil organic carbon and it was more accurate than the titrimetric method.